1990
DOI: 10.2307/1131111
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Achievement: A Study of Black, White, and Hispanic Children

Abstract: School achievement among black, white, and Hispanic elementary school children was investigated, and efforts were made to study the beliefs about academic achievement of the children and their mothers. A total of approximately 3,000 first, third, and fifth graders enrolled in 20 schools in the Chicago metropolitan area were given achievement tests in mathematics and reading. Black and Hispanic children performed at a significantly lower level than white children, but at fifth grade ethnic differences in mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(98 citation statements)
references
References 8 publications
9
85
0
4
Order By: Relevance
“…Researchers have found that African American and Hispanic parents place a high value on education, are concerned with educational issues, and have educational aspirations for their children that equal those of nonminority parents (De La Rosa and Maw, 1990;Stevenson et al, 1990;Wentzel, 1998). Despite these findings, recent data from the U.S. Bureau of Census (2004) indicates that a smaller percentage of African Americans and Hispanics attain a college degree than Caucasians.…”
Section: The Role Of Parental Goals Values and Aspirationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have found that African American and Hispanic parents place a high value on education, are concerned with educational issues, and have educational aspirations for their children that equal those of nonminority parents (De La Rosa and Maw, 1990;Stevenson et al, 1990;Wentzel, 1998). Despite these findings, recent data from the U.S. Bureau of Census (2004) indicates that a smaller percentage of African Americans and Hispanics attain a college degree than Caucasians.…”
Section: The Role Of Parental Goals Values and Aspirationsmentioning
confidence: 99%
“…A review of the research on parental socialization goals with respect to academic achievement, however, suggests that these goals do not vary dramatically by ethnicity (De La Rosa and Maw, 1990;Muller and Kerbow, 1993;Stevenson et al, 1990;Spera and Wentzel, in press;Wentzel, 1998). For example, Stevenson et al (1990) found that both nonminority and minority parents highly value school and have high aspirations for their children.…”
Section: Parental Socialization Goals: Do They Vary By Ethnicity?mentioning
confidence: 99%
See 1 more Smart Citation
“…While Asian immigrant parents are often available to draw on educational and financial resources within their community, Latino immigrant parents are more often on their own when it comes to support their children's schooling (Zhou and Kim 2006). In one early study, Stevenson et al (1990) found that immigrant Latino mothers' sense of efficacy in helping their children with reading and mathematics in elementary school was significantly lower than that of European American and African American mothers. Non-immigrant Latino parents feel more confident about their children's chances for success than do those of the immigrant generation; for example, Hao and Bonstead-Burns (1998) found that immigrant Mexican parents had lower expectations for their eighth grader's future schooling than did Mexican-heritage parents born in the USA.…”
Section: What Are the Predictors Of Parental Expectations?mentioning
confidence: 99%
“…Parent efficacy for helping their children succeed in school has been shown to predict home-and school-based involvement (Green, Walker, Hoover-Dempsey, & Sandler, 2007;Walker et al, 2005), indicating that parents are more likely to be involved if they have the belief that their actions will improve learning and academic performance (Green et al, 2007;Grolnick et al, 1997;Hoover-Dempsey, Bassler, & Brissie, 1992;Stevenson, Chen, & Uttal, 1990). In contrast, parents who view themselves as less able to effectively contribute to their child's education are more likely to refrain from participating in such activities.…”
Section: Parent Efficacymentioning
confidence: 99%